Elal Cycle - Chris Moss (Symphony in the Flint Hills, 2015)
As plains dwellers, the Tehuelche were hardy drifters who wandered across the barren steppe dressed in the skins of the guanaco, the pretty, rust-coloured relative of the llama that inhabits the southern reaches of the Americas. The Tehuelche creation story is known as the Elal Cycle, after a heroic man-god who arrives in Patagonia from a “Big Island” on the back of a swan.
Keywords: history; Elal; story; llama; people; Patagonia; Tehuelche creation